Effect of Work-Integrated Learning and Instructor Skills on Vocational Graduates' Work Readiness: The Mediating Role of Self-Efficacy - Yati Yati; Fitra Jaya; Agussalim Agussalim; Andi Tenri Ampa; Andi Annisa Sulolipu (FKIP Universitas Lampung, 2026)
Graduate work readiness has become a crucial issue given the high unemployment rate among Vocational High School (SMK) graduates, thus requiring a deep understanding of the factors that influence it. This study aims to analyze the effect of work-integrated learning and instructor skills on the work readiness of SMK graduates in West Java Province, with self-efficacy as a mediating variable. The main objective of this research is to explain the role of self-efficacy as a mediator between work-integrated learning experiences and instructor quality on work readiness. The study employed a quantitative, cross-sectional survey design. The sample consisted of 292 public Vocational High School graduates in West Java selected through a multistage cluster random sampling technique to ensure geographical representativeness and diversity of vocational programs. Data were collected using validated, structured questionnaires with Likert-scale responses that measured four main constructs: work-integrated learning, instructor skills, self-efficacy, and work readiness. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares. Work-integrated learning and instructor skills have positive and significant effects on the self-efficacy of Vocational High School graduates. Self-efficacy proves to have a positive and strong influence on work readiness, indicating that self-confidence (self-efficacy) is an important predictor of work readiness. Although work-integrated learning and instructor skills also have direct effects on work readiness, these effects are relatively small compared with the indirect effects mediated by self-efficacy. Self-efficacy is a key factor in reducing the unemployment rate among Vocational High School graduates. The practical implications highlight the importance of graduates' self-confidence, work-integrated learning, and the strengthening of instructors' pedagogical and professional competencies as solutions for improving the work readiness of Vocational High School graduates. Keywords: integrated learning, instructors skill, work readiness, self-confidence.